Reduced cholinergic function in normal and Alzheimer's disease brain is associated with apolipoprotein E4 genotype. - Allen, S; MacGowan, S; Tyler, S; Wilcock, G; Robertson, A; Holden, P; Smith, S; Dawbarn, D (1997)
Apolipoprotein E (ApoE) is a potent risk factor for Alzheimer's disease. Since the loss of cholinergic function in Alzheimer's disease is known to occur at an early stage in the disease we have examined this function in normal subjects with an Apoepsilon4 allele to see if the deficit occurs in the absence of Alzheimer pathology or symptoms. We report that brain tissue obtained post-mortem from normal subjects and Alzheimer patients with an Apoepsilon4 allele has a lower cholinergic activity than tissue from those subjects without this allele. This has important significance for the interpretation of the cholinergic deficits found in Alzheimer's disease.